An evaluation of therapeutic and reactivating effects of newly developed oximes (K156, K203) and commonly used oximes (obidoxime, trimedoxime, HI-6) in tabun-poisoned rats and mice - Kassa, Jiri; Karasova, Jana; Musilek, Kamil; Kuca, Kamil (Toxicology, 2008)
The potency of newly developed monoxime bispyridinium compounds (K156, K203) in reactivating tabun-inhibited acetylcholinesterase and reducing tabun-induced lethal toxic effects was compared with commonly used oximes (obidoxime, trimedoxime, the oxime HI-6) using in vivo methods. Studies determining percentage of reactivation of tabun-inhibited blood and tissue acetylcholinesterase in poisoned rats showed that the reactivating efficacy of newly developed oxime K203 is comparable with obidoxime and trimedoxime in blood and higher than the reactivating potency of trimedoxime and obidoxime in diaphragm and brain, where the difference in reactivating efficacy of obidoxime, trimedoxime and K203 is significant. On the other hand, the potency of newly developed K156 to reactivate tabun-inhibited acetylcholinesterase is comparable with obidoxime or trimedoxime in diaphragm and brain. It is significantly lower than the reactivating efficacy of trimedoxime and obidoxime in blood. Moreover, both newly developed oximes were found to be relatively efficacious in the reduction of lethal toxic effects in tabun-poisoned mice. Especially, the oxime K203 is able to decrease the acute toxicity of tabun nearly two times. The therapeutic efficacy of K156 and K203 corresponds to their potency to reactivate tabun-inhibited acetylcholinesterase, especially in diaphragm and brain. In contrast to obidoxime and trimedoxime, the oxime HI-6 is not effective in reactivation of tabun-inhibited acetycholinesterase and in reducing tabun lethality. While the oxime K156 does not improve the reactivating and therapeutic effectiveness of currently available obidoxime and trimedoxime, the newly developed oxime K203 is markedly more effective in reactivation of tabun-inhibited acetylcholinesterase in rats, especially in brain, and in reducing lethal toxic effects of tabun in mice and, therefore, it is suitable for the replacement of commonly used oximes for the antidotal treatment of acute tabun poisoning.
Keywords: Cholinesterase Reactivators; acetylcholinesterasa; Organophosphate Poisoning; cholinesterasové inhibitory; Drug Therapy, Combination; oximy; krysa rodu Rattus; kombinovaná farmakoterapie; molekulární struktura; záchvaty; reaktivátory cholinesterasy; Organophosphates; Chromatography, High Pressure Liquid; Lethal Dose 50; myši; Toxicity Tests, Acute; Mice; antidota; potkani Wistar; Antidotes; organofosfáty; trimedoxim; Oximes; druhová specificita; Molecular Structure; Species Specificity; Trimedoxime; Rats, Wistar; Acetylcholinesterase; mužské pohlaví; vysokoúčinná kapalinová chromatografie; zvířata; LD50; Rats; Animals; Injections, Intramuscular; Male; Atropine; testy akutní toxicity; pyridinové sloučeniny; Seizures; Cholinesterase Inhibitors; injekce intramuskulární; otrava organofosfáty; atropin; Obidoxime Chloride; obidoxim chlorid; Pyridinium Compounds